Nursing students' knowledge and attitudes on sexually transmitted infections prevention at training institution in Namibia - Lonia U. Hamunyela; Hileni N. Niikondo; Monika N. Nakweenda (AOSIS, 2024)
Background: Insufficient knowledge about sexually transmitted infections (STIs) among nursing students can impact patient care and outcomes. To address this, comprehensive STI education is crucial. Aim: This study aimed to assess knowledge and attitudes of nursing students regarding STI prevention and control. Setting: The research was conducted at a nursing training institution in Windhoek, Namibia. Methods: The research employed a cross-sectional design with 73 participants. Results: Outcomes revealed that 63.0% had satisfactory knowledge and 79.5% exhibited positive attitudes. A significant association was noted between knowledge and participants' sex. Male participants displayed poor knowledge (70%). No significant relationship existed between demographic characteristics and attitudes. Conclusion: The study concluded lower than expected knowledge regarding STIs among nursing students that implicated patients' care. Contribution: Integrating STI education into nursing curricula can improve students' competences that enhance patients' care.